In silico evaluation of garlic-derived organosulfur compounds as multi-target inhibitors of breast cancer biomarkers - Courage Siame; Benedict Ofori; Lily Paemka; Kwabena Owusu Danquah (PLoS ONE, 2026)
Breast cancer is the leading cause of cancer mortality among women globally, and drug resistance complicates treatment. Garlic-derived organosulfur compounds exhibit anticancer potential, but their multi-target activity against key breast cancer biomarkers remains unclear. This study utilized AutoDock Vina for molecular docking, OpenBabel for post-docking energy minimization, and employs SWISS-ADME and PreADMET platforms for ADMET profiling to assess six garlic compounds (Z-ajoene, allyl-methyl trisulfide, diallyl disulfide, diallyl sulfide, diallyl trisulfide, and S-allyl-L-cysteine) against clinically relevant breast cancer targets. Z-ajoene showed strong binding to Bcl-2, Topoisomerase II, and CDK-2, while S-allyl-L-cysteine targets five biomarkers. All compounds complied with Lipinski’s rule of five, indicating good oral bioavailability, and display favorable ADMET properties with no mutagenic or tumorigenic risks. Most compounds were predicted to inhibit P-glycoprotein, while only Z-ajoene showed potential inhibition of CYP2C9, suggesting possible drug-drug interactions. Despite moderate affinities, these compounds may serve as potential promising multi-target agents in breast cancer therapy. Our computational findings provide preliminary evidence that garlic-derived compounds warrant further in vitro and in vivo evaluation, particularly in the context of drug-resistant breast cancer.